Industrial design in the American legal system: the itch for protection - Abu Algasim Elawad, Saad; Ansari, Abdul Haseeb (penseejournal.com, 2014)

(untitled)
For the protection of industrial design in the American legal system, the main three laws of intellectual property being copyright, patent and trademark have been set in motion; a privilege that has not been enjoyed, if any, by so many rights. Yet there seems to be a general consensus on the inadequacy of the legal protection afforded. This general consensus is seen as a manifestation of an economic phenomenon that consists in the keen interest of manufacturers and industrial designers in the financial value subsisting in their designs. An economic phenomenon that is thought to be unhealthy and, therefore, it is referred to as the itch for protection. This unhealthy itch has manifested itself in two main unhealthy legal symptoms: one is identified with the unjustifiability of the criticism of the legal protection of industrial design, and the other is identified with the unintelligibility of the initial divergence and the eventual convergence on whether industrial design can be protected by both copyright and patent. This paper aims at touching gently on the unhealthy character of the economic phenomenon and handling rather roughly the unhealthy character of the legal symptoms through which the unhealthy economic phenomenon has manifested itself. The paper intends to do that through first providing the reader with the very necessary information about industrial design with respect to its meaning, rationales, modes of protection and the criteria of such protection. Having this necessary information in the background, the paper will be in a better position to point analytically and critically to where the signs of unjustifiability and unintelligibility lie. Having done that, the paper will not be in a better position to assert that the legal protection of industrial design in the American legal system is adequate. Nevertheless, it will be in a better position to assert that the criticism of such protection is baseless, and the effort to provide it by both copyright and patent is pointless.